Los misioneros salesianos y la polémica sobre la extinción de los Selk’nam de Tierra del Fuego - Nicoletti, María Andrea (2006)
The selk'nam's extinction generated a controversy regarding its causes within the Salesian Congregation. The evangelization and civilization process of the selk'nam began through the creation of the Nuestra SEñora de la Candelaria reduction in 1893 by Monsignor Fagnano. In this reduction the natives seeked protection from the fueguino ladowners' pursuit and murder. The murders, the spread of new illnesses to which natives were not immune and the cultural impact of the reductional system caused the selk'nam's extinction. The Salesian missionaries, responsible for the reduction process, analyzed the causes of this extinction. They stressed that the slaughters carried out by the fueguinos and the violence perpetrated by local authorities were the main causes of population decrease, while recognizing the impact of the reduction system in the local culture. The next generation of Salesians revisited the sources. They dismissed the violence as a major cause of the ectinction in favor of physiological and cultural causes. Their purpose was to cover the role of the Braun Menéndez Behty ladowner families- sponsors to the Salesians- in this process.